Inflation Dynamics in Madagascar, 1971-2000 - Sacerdoti, Emilio (IMF Working Papers; Working Paper, 2001)
The paper analyzes the dynamics of inflation in Madagascar in the period 1971-2000, applying cointegration analysis and error correction modeling. The empirical results, based on quarterly data, confirm that there exists a stable money demand relationship, as well as a purchasing power relationship in the long run. The former enters the short-run dynamics of inflation and money growth, while the latter affects the short-run dynamics of the exchange rate only. We also find that an appreciation has a direct negative impact on inflation and that inflation inertia is important. In addition, we conduct FIML estimation of the system and trace the impulse responses to various shocks.